2012
DOI: 10.1182/blood-2012-01-404723
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DP genetic variation, proxies for early life immune modulation and childhood acute lymphoblastic leukemia risk

Abstract: The human leukocyte antigen (HLA) genes are candidate genetic susceptibility loci for childhood acute lymphoblastic leukemia (ALL). We examined the effect of HLA-DP genetic variation on risk and evaluated its potential interaction with 4 proxies for early immune modulation, including measures of infectious exposures in infancy (presence of older siblings, daycare attendance, ear infections) and breastfeeding. A total of 585 ALL cases and 848 controls were genotyped at the HLA-DPA1 and DPB1 loci. Because of pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
(63 reference statements)
2
24
0
Order By: Relevance
“…HLA-DPB1*01∶01 has previously been reported to be underrepresented among UKCCS ALL patients [41] and was recently reported to be associated with an increased risk for ALL in the NCCLS [14]. In addition, our results are suggestive that this haplotype may be overrepresented among T-ALL patients in the UK population (8.39%; P = 0.1).…”
Section: Discussionsupporting
confidence: 60%
“…HLA-DPB1*01∶01 has previously been reported to be underrepresented among UKCCS ALL patients [41] and was recently reported to be associated with an increased risk for ALL in the NCCLS [14]. In addition, our results are suggestive that this haplotype may be overrepresented among T-ALL patients in the UK population (8.39%; P = 0.1).…”
Section: Discussionsupporting
confidence: 60%
“…The risk allele of this SNP was robustly associated with changes in expression of HLA-DPA1 (increased expression), HLA-DRB1 (increased expression) and HLA-DQA2 (decreased expression) in brain tissues. HLA-DPA1 is an HLA class II α chain paralogue presenting peptides derived from extracellular proteins; 27 this is of particular relevance as impairment of clearance of extracellular debris might increase risk of developing a neurodegenerative condition, 28 including FTD and PD. While HLA-DRB1 has functions similar to HLA-DPA1, HLA-DQA2 belongs to the HLA class II α chain family located in intracellular vesicles: it plays a central role in the peptide loading of MHC class II molecules and releasing the class II-associated invariant chain peptide (CLIP) molecule from the peptide-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a relationship between HLA polymorphisms and susceptibility to certain hematologic malignancies such as chronic lymphocytic leukemia, multiple myeloma, and acute lymphoblastic leukemia. [9][10][11] However, there is little information about the relationship between HLA polymorphisms and susceptibility to developing B-NHL or their outcomes. [12][13][14][15][16] Focusing on diffuse large B-cell lymphoma (DLBCL), some associations between HLA specificities and this B-NHL subtype have been described, as well as with other genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we describe for the first time the role of HLA polymorphisms in the prognosis of DLBCL patients receiving rituximabbased regimens as first-line treatment. Our results show that the presence of the HLA-DRB1*01 and the absence of HLA-C*03 polymorphism are associated with susceptibility to DLBCL, while the HLA-B44 supertype, especially the presence of HLA-B*18 and HLA-B*44 polymorphisms, have an independent influence on survival.The HLA system has been related to susceptibility to several hematologic and nonhematologic diseases, [9][10][11]36 including a variety of HLA polymorphisms associated with B-NHL development and outcome. [12][13][14][15][16] However, this feature has not been extensively studied specifically in DLBCL, although some data suggest an association between HLA subtypes and disease susceptibility (ie, a higher incidence of HLA-DRB1*04:01 allele in this lymphoma subgroup).…”
mentioning
confidence: 99%